TAN MALAKA: THE CONCEPT OF 100% INDEPENDENCE IN PERFECTING THE INDEPENDENCE OF THE REPUBLIC OF INDONESIA - Aji, Wahyu Trisno Aji (UIN Mataram, 2024)
This study examines Tan Malaka's idea of 100% independence as an effort to perfect Indonesian independence in the context of history and politics after the proclamation of August 17, 1945. Tan Malaka, as one of Indonesia's revolutionary figures, argued that the independence declared in 1945 had not achieved the true meaning of complete freedom. He criticized the independence that was considered to be enjoyed only by a handful of elites and intellectuals, while the people were still marginalized from the welfare promised by independence. In his work